PENGARUH PENAMBAHAN SERAT SINTETIK PLASTIK TERHADAP KEKUATAN TEKAN DAN LENTUR BETON - N. Retno Setiati (Direktorat Bina Teknik Jalan dan Jembatan, 2010)
The use of additional materials to improve concrete performance has rapidly developed, such as synthentic fiber of plastic which commonly used for concrete structure. The use of such material in concrete is expected to be able to increase concrete strength. The purpose of the research is to find out the optimum composition and the effectiveness of plastic fiber in concrete performance. Laboratory tests has been conducted. Based on analysis result showed that at the age of 28 days, the compressive strength with composition of 4 kg/m3 (39,228 N/m3) is 2,6% greater than normal concrete and flexural strength increased 1,6% to normal concrete. Key words : synthetic fibre, composition, compressive strength, flexural strength, fibre concrete